(Un)Secure Booking: Security Risks Within Facebook Groups Accommodation Reservations - Franjić, Mihaela; Pavlakovič Farrell, Barbara (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The tourism industry has significantly reshaped with the development of ICT and the Internet. In the contemporary digital world, most tourists utilise Smart Tourism Technologies services to search and book their travels, pay for services, and discover attractions at destinations. The level of security is a significant factor affecting the tourist experience since tourists employ technology to obtain information in all stages of their travel, especially in the first phases, and trust that it is reliable and truthful. Among the most known threats are fake profiles, identity theft, personal data theft, AI fraud, and others. Facebook, a pioneer in social media, hosts various groups related to promoting tourism (advertisements, tourist communities, reviews) or tourism offers (transportation, accommodation, guided tours, equipment sales). There are increasing cases of Facebook booking scams, where users are paying money for tourism services but ending up without paid service. Therefore, this paper focuses on the booking phase by analysing providers' actions within Facebook groups regarding popular tourist destinations such as Amsterdam, Milan, Prague, Istanbul, London, and Dublin. By analysing written and visual content and carefully reviewing group posts and requests, we identified signs of potential security risks that users should be aware of when searching for providers.